Pengaruh Implementasi Pendekatan Saintifik Terintegrasi Al-Qur’an dalam Pembelajaran Biologi terhadap Keterampilan Proses Sains Siswa MAN 2 Bone - A. Irawati AM; Nurmi Nurmi; Sri Wahyuni (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Science Process Skills (SPS) is one of the important scientific thinking skills for students to process information received in learning. Science process skills in biology learning are one of the important aspects for the development of students' scientific thinking abilities. A scientific approach integrated with the values ​​of the Qur'an was chosen as a solution because it is relevant to the nature of biology as a science that studies the universe created by Allah SWT. This study aims to measure students' science process skills, analyze, and prove the effect of using a scientific approach integrated with the Qur'an on the science process skills of class X students of MAN 2 Bone. The type of pre-experimental research with one group pretest-posttest design was used based on the research objectives. The research sample consisted of 22 students selected through purposive sampling technique. The instrument used in this study was a test (pretest and posttest) to measure students' abilities. The data obtained were then analyzed using descriptive and inferential statistics through the SPSS 23 program. The results showed that the average score of students' Science Process Skills (SPS) in the pretest was 28.50 (median 27.50; SD 10.88), with 2 aspects being very poor, 2 being poor, 1 being sufficient, and 1 being good. The lowest percentage was in the questioning aspect (14.20%), the highest was in the classifying aspect (72.15%). After the application of the Al-Qur'an integrated scientific approach to 22 students, the posttest average increased to 42.68 (median 46; SD 11.91), with the lowest percentage in asking (40.90%, poor category) and the highest in observing (82.19%, good category). The data were normal (pretest 0.487; posttest 0.097) and homogeneous (sig. 0.079), and the paired sample t-test showed a significant increase (sig. 0.000 < 0.05). These findings indicate that the scientific approach significantly influences students' science process skills.